Dynamic Software Based Mathematics Review Lesson Design: Take a Basic Theorem of Vector Plane as an Example - Zou, Shuo; Pereira, Jerito; Hermita, Neni (Indonesian Journal of Science and Mathematics Education, 2022)
Reviewing lessons as a very important form of learning and very important role to impress students. The research method was adopted the ADDIE model design. This research was done at Balihan Senior High School, China. The population of this research are 43 students and using random sampling to selected a representative 5 students. The student statement result show that, a using Hawgent dynamic in the review lesson can improve student learning performance, very useful in the learning process and etc with statement average is 80.4% or good category. Based on validation results of the 3 aspects obtained an average percentage of 81.33% in a good category. Therefore, the review lesson of basic theorem vector plane using Hawgent dynamic mathematics software can be applied to the teaching process and can using this dynamic software to the review lesson another mathematics topics.